Travelers' intention to adopt virtual reality: A consumer value perspective. (September 2020) - Vishwakarma, Pankaj; Mukherjee, Srabanti; Datta, Biplab
Abstract: Through the lens of the value-based adoption model (VAM), this study examines consumers' perceived value and the intention to adopt virtual reality (VR) for evaluating various tourist destinations. The hypothesized model was tested through structural equation modeling using the responses of 208 Indian tourists. This work indicates the importance of perceived immersion and perceived physical risk as the two most vital indicators of benefits and sacrifice respectively. Moreover, perceived value was found to be one of the most important predictors in the adoption of VR. This study also identified that sensation-seeking behavior has a significant favorable influence on the behavioral intention to adopt VR for evaluating various tourist destinations. The study's findings will help departments of tourism and tourism companies attract more tourists through the power of VR. Highlights: Investigates VR adoption from the consumer value perspective. Perceived immersion and perceived physical risk are key factors of benefits and sacrifices respectively. The perceived cost of using VR has no significant influence on perceived value. Sensation-seeking has a positive and significant impact on intention to use VR. Gender has no significant impact on VR adoption.